آليات مقاومة الإجهاد الملحي عند النباتات المحلية دراسة مقارنة و مراجعة حالة النباتات المحلية النامية في الصحراء الجزائرية - تليلي, نور الهدى; عي, حياة; مسلم, عائشة; هزبري, وئام (جامعة الوادي - University of Eloued, 2022)
In attempt to compare and revisit the extreme impact of salt-tolerance and its factors in halophytes desert plants through identifying the way salinity effects the plant's morphology and its biochemical interactions. This study aims at re-examining the afore published studies about the mechanism and the resistance of salt-tolerance in: Suaeda mollis (Desf.) Del., Atriplex halimus L., Limoniastrum guyonianum Dur., Tamarix boveana Bunge and Zygophyllum album L. Through which a different mechanism of salt-tolerance was determined in each sample via employing the comparative analysis methods on the results of these studies. Those yield, eventually, at the reduction of the salts concentration within the tissues by excreting excess salts through the leaves or roots and the adaptation to the conditions of the medium so that the plant resorts to many physiological mechanisms (reducing the absorption of toxic and accumulated ions in the cavities of the roots, reducing the ions accumulated in the young organs and the growing tops of aerial part), or by resistance to osmotic stress through tolerance or avoidance of drought, osmotic regulation, avoidance of toxins or through resistance by acceleration of vegetative growth.
التنوع الحيوي و فيزيولوجيا النبات
Keywords: النباتات المحلية الصحروية الجزائرية; Salinity; Mechanism of Resistance; Salt-Stress; Halophyte Algerians Desert.